Peran Pemuda dalam Konservasi Mangrove di Pesisir Pulau Ambon: Edukasi dan Peningkatan Kesadaran bagi Kader AMGPM - Ronald Darlly Hukubun; Sherly Lewerissa; Laury Marcia Ch. Huwae (Pusat Riset dan Inovasi Nasional, 2025)
The mangrove ecosystem on the coast of Ambon Island faces serious threats due to pressure from human activities and unsustainable development. Responding to these conditions, this Community Service (PKM) activity was carried out with the aim of increasing the role of youth, especially cadres of the Maluku Protestant Church Youth Force (AMGPM), in mangrove conservation efforts. Through an educational approach and increasing ecological awareness, participants were given an understanding of the important functions of mangrove ecosystems, the ecological benefits they produce, and various threats arising from environmental exploitation and degradation. This PKM activity is carried out in several stages, namely preparation, implementation (interactive lectures and discussions), evaluation, and closing. The results of the activity showed a significant increase in the knowledge and concern of AMGPM cadres of Twing I Lateri and Calvary Branch towards mangrove conservation. In addition, this activity succeeded in fostering the spirit of participants to become agents of change in their respective communities. With the active involvement of youth, this PKM is expected to be able to encourage the sustainability of mangrove conservation programs in the coastal area of Ambon Island. This effort is a strategic step in preserving coastal ecosystems, strengthening environmental resilience, and building community collective awareness of the importance of sustainable natural resource conservation.